Using videos as a strategy to teach the pronunciation of Plosive Bilabial Minimal Pairs in seventh-grade students at Juan Pablo II High School,academic period 2022-2023 - Montenegro Fernández, Stefany Mishelle (2024)
Propose the use of videos as a strategy to teach the pronunciation of Plosive Bilabial Minimal Pairs in seventh-grade students at Juan Pablo II High School.